Jeremy Bentham on Religion and Law Reform (Stato, Chiese e pluralismo confessionale, 2009)
This paper was originally delivered at the Conference “Religions, Law, and Democracy”, organized by Università degli Studi di Milano, held in Gargnano del Garda (on October 1-2, 2007).